IMPROVING THE ENERGY EFFICIENCY OF RAILWAY TRANSPORT THROUGH PHYSICAL AND MATHEMATICAL METHODS - Котвицька, Клавдія; Єрохін, Ярослав (SWorldJournal, 2025)
The article examines modern approaches to improving the energy efficiency of railway transport using physical and mathematical methods. The principles of regenerative braking, improvement of the aerodynamic characteristics of rolling stock, use of lightwe